Enhancing Science Learning Outcomes Through Project-Based Learning Integrated with Educational Board Games: A Classroom Action Research on Biotechnology at the Junior Secondary Level - Rifajrin Rifajrin; Rifda Nur Hikmawati Arif (BIOCHEPHY: Journal of Science Education, 2026)
Low science learning achievement and insufficient active student engagement have necessitated the adoption of innovative instructional strategies. This study aimed to evaluate the effectiveness of a Project-Based Learning (PjBL) model integrated with educational board games on the learning outcomes of eighth-grade students at State Junior High School 26 Makassar, with a focus on Biotechnology content. A Classroom Action Research (CAR) design following the Kemmis and McTaggart spiral model was employed across three consecutive cycles, involving 29 students. Data were collected through pretest–posttest instruments and formative assessments administered at the conclusion of each cycle. Results indicated a progressive improvement in learning outcomes, with mean scores rising from 67.1 in Cycle I to 72.4 in Cycle II and 77.9 in Cycle III, alongside an improvement in class mastery rates from 44.8% to 58.6% and 68.9%, respectively. Normalised gain (N-Gain) analysis across cognitive indicators C1–C4 yielded an overall mean of 0.33, classified as moderate. The integrated PjBL and educational board game model demonstrably enhanced cognitive learning outcomes and fostered active, collaborative, and enjoyable learning environments. These findings support the adoption of this integrated approach as a viable pedagogical alternative in science education at the junior secondary level.